The role of liquidity and implicit guarantees in the German twin crisis of 1931 - Isabel Schnabel (Max Planck Institute for Research on Collective Goods, 2005)
Using monthly balance-sheet data of all major German credit banks, we analyze deposit withdrawals and bank failures in the German banking and currency crisis of 1931. We find that deposit withdrawals were driven by the run on the currency, but were also related to banks' liquidity positions; that branch banks were no more stable than unit banks; and that large banks were privileged, being bailed out and receiving preferential access to the discount window. These findings underline the importance of liquidity and implicit guarantees in twin crises, while they question the benefits of branching in such crises.
Keywords: G21; E5; N24; C34; 330; Twin crises; liquidity; implicit guarantees; too big to fail